Capturing multiple social perspectives on adaptation across scales: a Q-method analysis of actors from development planning in the Philippines. (4th July 2018) - Dujardin, S.; Orban-Ferauge, F.; Cañares, M.P.; Dendoncker, N.
Abstract : This paper describes and analyses viewpoints regarding climate change adaptation held among key social actors from the field of development planning in the Philippines. Four empirically signiﬁcant social perspectives are determined – institutional, grassroots, developmental, and physical planning – using Q -method, an intensive qualitative and quantitative technique. Major differences and commonalities between perspectives are highlighted, in addition to actors' arguments used to justify claims. Drawing upon an actor-oriented approach, results contribute filling a knowledge gap in the literature on the need to develop approaches that can guide adaptation thinking in development planning. While the four perspectives identified provide evidence that differentiated viewpoints on climate change and planning practices may lead to divergent adaptation strategies, commonalities among social perspectives suggest that shared adaptations may also emerge both among actors from multiple organizational structures and across the organisational hierarchy of planning. By building learning processes that include multiple social perspectives across scales, development planning can become a promising candidate for strengthening adaptive capacities and delivering more effective responses to climate change.